Loss of IκBα-Mediated Control over Nuclear Import and DNA Binding Enables Oncogenic Activation of c-Rel - Sachdev, Shrikesh (American Society for Microbiology, 1998)
The IκBα protein is able both to inhibit nuclear import of Rel/NF-κB proteins and to mediate the export of Rel/NF-κB proteins from the nucleus. We now demonstrate that the c-Rel–IκBα complex is stably retained in the cytoplasm in the presence of leptomycin B, a specific inhibitor of Crm1-mediated nuclear export. In contrast, leptomycin B treatment results in the rapid and complete relocalization of the v-Rel–IκBα complex from the cytoplasm to the nucleus. IκBα also mediates the rapid nuclear shuttling of v-Rel in an interspecies heterokaryon assay. Thus, continuous nuclear export is required for cytoplasmic retention of the v-Rel–IκBα complex. Furthermore, although IκBα is able to mask the c-Rel-derived nuclear localization sequence (NLS), IκBα is unable to mask the v-Rel-derived NLS in the context of the v-Rel–IκBα complex. Taken together, our results demonstrate that IκBα is unable to inhibit nuclear import of v-Rel. We have identified two amino acid differences between c-Rel and v-Rel (Y286S and L302P) which link the failure of IκBα to inhibit nuclear import and DNA binding of a mutant c-Rel protein to oncogenesis. Our results support a model in which loss of IκBα-mediated control over c-Rel leads to oncogenic activation of c-Rel.